2020
DOI: 10.1016/j.vetmic.2020.108708
|View full text |Cite
|
Sign up to set email alerts
|

Peptide inhibitors of tembusu virus infection derived from the envelope protein

Abstract: The outbreak and spread of Tembusu virus (TMUV) has caused very large losses in the waterfowl-breeding industry since 2010. The viral envelope (E) protein, the principal surface protein of viral particles, plays a vital role in viral entry and fusion. In this study, two peptides derived from domain II (DII) and the stem of the TMUV envelope protein, TP1 and TP2, respectively, were tested for their antiviral activity. TP1 and TP2 inhibited TMUV infection in BHK-21 cells, and their 50% inhibitory concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Therefore, the viral RNA genome was translated to initiate virus replication, at the same time the ubiquitin-proteasome system also played an important role in DTMUV replication [ 49 ]. In addition to mediating virus entry, E protein is essential for DTMUV pathogenesis [ 50 ]; especially, mutations in several important amino acid sites, which can significantly affect viral pathogenicity. Yan et al reported that a single mutation at amino acid residue 156 (S-P) reduced the ability of viral replication and transmission in ducks, and further analysis confirmed that the potential mechanism was composed by the disruption of N-linked glycosylation at position 154 and changes in the conformation of the “150 loop” of the E protein [ 51 ].…”
Section: Overview Of Dtmuvmentioning
confidence: 99%
“…Therefore, the viral RNA genome was translated to initiate virus replication, at the same time the ubiquitin-proteasome system also played an important role in DTMUV replication [ 49 ]. In addition to mediating virus entry, E protein is essential for DTMUV pathogenesis [ 50 ]; especially, mutations in several important amino acid sites, which can significantly affect viral pathogenicity. Yan et al reported that a single mutation at amino acid residue 156 (S-P) reduced the ability of viral replication and transmission in ducks, and further analysis confirmed that the potential mechanism was composed by the disruption of N-linked glycosylation at position 154 and changes in the conformation of the “150 loop” of the E protein [ 51 ].…”
Section: Overview Of Dtmuvmentioning
confidence: 99%
“…In the case of TP2, this peptide showed antiviral activity against TMUV as well as Japanese encephalitis virus (another Flaviviridae virus), and due to the highly conserved stem regions of TMUV and other flaviviruses, TP2 may probably inhibit other flaviviruses. Therefore, TP2 and TP2 derivatives or analogous peptides might probably work as broad-spectrum flavivirus inhibitors [85].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%